(untitled) (TAJ: Journal of Teachers Association, 2009)
Irritable bowel syndrome (IBS) is the most common functional gastrointestinal disorder commonly associated with psychosomatic illness Eighty six patients of IBS who met the clinical Rome-II criteria were enrolled in this prospective study. Necessary laboratory investigations were done to exclude organic diseases. All patients were subjected to psychiatric assessment by clinical psychiatrist using DSM-IV criteria. 96.5% of the studied patients actually had different psychiatric illness. Among them generalized anxiety disorder (24.4%), depressive illness (27.8%), somatoform disorder (12.7%) and hypochondriasis (10.4%) were the predominant abnormalities. New onset of IBS patients exhibited higher prevalence of generalized anxiety disorder (42.8%) in comparison to longer duration of illness. Depressive illness (44.4%) was substantially higher in constipation-predominant IBS than other forms. doi: 10.3329/taj.v18i1.3296 TAJ 2005; 18(1): 10-13